Religion and Postmodernism - Shah, Mohd Hazim (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2022)
In this article, I discuss the implications of postmodernism on religious thought, with special reference to Islamic thought. Firstly, I discuss the nature and characteristics of postmodernist thinking, and the different schools of thought/’postmodernisms’ that fall under that rubric. My contention is that postmodernism is a response to modernism rather than religion, although it has implications on religious thought. Secondly, I examine and compare the points of contention between modernism and post-modernism. I then argue that the differences are largely due to the privileging of nature and reasoning of modernists and the privileging of human/social and psychology of postmodernists. These, in turn, have implications on their metaphysics and epistemology, respectively. Thirdly, I provide an Islamic perspective on the modernist-postmodernist discourse, showing that the Islamic perspective transcends the natural-social divide, and how the tripartite relationship between God, man and nature, informs the discourse. The philosophy of language is also brought up in the discussion, where I suggest that Islam accepts the dual role of languages, that is, conveying the meaning in its literal sense (aka modernist), as well as being a symbol and an indirect reference (aka postmodernist). Finally, a close comparison is made between postmodernism and Islam, where both their incompatibilities as well as possible points of convergence are discussed.